Research on the Horizontal Bearing Capacity of Pile Head Reinforcement Measures with Different Variable Stiffiness Structures - LI Xiang; LIU Jiaqi; GUO Zhaosheng; WANG Wei; ZHANG Zehua; ZHAO Jing (Taiyuan Ligong Daxue xuebao)
[Purposes] To solve the problem that the joint between rigid connection pile cap and pile head is easy to be damaged, single pile model tests are carried out in a geotechnical box to study the seismic performances of the connection between pile head and pile cap, “pile companion”, and connection wall. [Methods] On this basis, based on the actual transmission line foundation project 2×2 low-cap PHC elastic medium-long pile group was adopted to further elaborate, the above-mentioned variable stiffness structure enhancement mechanism, and the finite element method was used to study the horizontal bearing characteristics of the pile head before and after the setting of variable stiffness structure in the pile group. [Findings] The results show that the variable stiffness structure outside the pile head can improve the seismic and horizontal bearing capacities of the pile top by expanding the cross section of the pile head, improving the bending stiffness of the pile head, and greatly reducing the negative bending moment of the pile top. When the horizontal load is applied to 1.6 Hu=3 200 kN, the variable stiffness structure outside the pile head can improve the horizontal bearing capacity of the pile top by 27.50%~29.92%. At the same time, the working range of the soil around the pile is increased, and the horizontal deformation of the foundation soil is reduced by 22.1%~26.53%. The circular sleeve and connecting wall can play a role in any soil condition. In practical engineering, it is necessary to comprehensively consider the limit heigth and thickness-to-diameter ratio of variable stiffness structure to avoid the waste of building materials.